THE ROLE OF IT INFRASTRUCTURE FLEXIBILITY AND LEARNING ORIENTATION TOWARDS ORGANISATIONAL AGILITY - HASSAN, NOOR HAFIZAH (2020)
In the recent era, agility is found to be one of the most important characteristics of a successful and competitive organisation. Agility refers to the responsiveness capability of organisations internally and externally. There are arguments stated by scholars on the role of Information Technology (IT) as enabler and hinder of agility. IT helps organisations to simplify business processes. IT facilitates technologies and enable more systematic ways of doing business. Information and knowledge constituted by learning and experience are organisational resources that are manipulated in IT and Information System (IS). Thus, various studies have examined on the importance of IT and learning towards organisational performance. However, limited number of studies have particularly analysed the driving factors of Information Technology Infrastructure Flexibility (ITIF) and Learning Orientation (LO) towards Organisational Agility (OA).